Strategi Pengguna Media Sosial Dalam Mengatasi Tantangan Privasi dan Keamanan Online di Era Digital - Lisa Aulia Putri; Muh. Ali Fikri Subair; Nur Riswandy Marsuki (Concept: Journal of Social Humanities and Education, 2024)
The existence of social media does not always have a good impact, on the side of privacy and security that someone has on social media is often abused. Even more so in today's digital era. Various aspects of human life, such as education, business, entertainment, communication, and public relations, are influenced by the rapid development of information and communication technology in the digital era. The occurrence of hoaxes and misuse of personal data of social media users is a negative impact that is rife today. This article seeks to examine strategies that social media users can take in dealing with online privacy and security challenges. The method used is qualitative research, more precisely literature research. Data analysis techniques used data reduction, which means data analysis is done to summarize, choose the most important themes and patterns, and discard the unimportant ones. Researchers select information that is really important to include in this scientific work. Furthermore, Display Data (Data Presentation) is when a set of data is arranged so that conclusions can be drawn. The result is that social media users must adopt a variety of proactive strategies to deal with online privacy and security challenges in the digital age.